Dakwah dan Hukum Lingkungan - Aripudin, Acep (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2008)
The most important of Central isue in global era is globalÂ warning effect. One of itsâcauses isÂ hyper-usingÂ of technology un-controlled, that become damage in this world. The other causes is un-controlled ofÂ exploitation to nature and is not be attend to ecosystem and environment live. Respons and reaction to global condition was spoken by a lot of people, –include â Islam, specially if looked according to Islamic law. Masalah-mursalah concept, as teoritic can be made basic inÂ giving solutionÂ this global accident.